A Review of Oscillating Screen-Blower Cleaners for Gains - Pasikatan, Melchor C.; Quick, Graeme R. (Philippine Engineering Journal; Vol 16 No 2 (1995), 2021)
The available information may be limited, but sufficient to provide rough parameters for design under different operating conditions.  Researches show that to achieve good cleaning performance at high level material capacity in wheat and paddy. Air velocity of 7.2-9.2 m/s, air direction of 40-45⁰, height of drop of 70-102 mm, and hanger angels of 15-25⁰ should be used. Attempts to relate cleaning performance with two or more influencing factors are rare in the literature. Results derived with wheat and based on straw walker and shoe assembly of combines need to be validated for rice, rice threshers and cleaners. Further studies that will lead to a universal cleaning equation and a good understanding of particle motion as influenced by several variables are needed.